1994
DOI: 10.1161/01.str.25.2.352
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the disability of first-time stroke sufferers at 1 year. 12-month follow-up of a population-based cohort in southeast England.

Abstract: Background and Purpose The purpose of this study was to predict the functional outcome at 1 year of first-time stroke patients aged younger than 75 years in relation to the severity of stroke and demographic characteristics.Methods Population registers in three districts of southeast England were established in August 1989, with notification by stroke registry field-workers, general practitioners, and rehabilitation practitioners. Assessments were made using the Barthel index for activities of daily living at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(67 citation statements)
references
References 26 publications
3
63
0
1
Order By: Relevance
“…Incontinence is a stiong predictor of poor recovery (Gross, 1998;Taub et al, 1994). For example, the presence of incontinence in first-time stroke survivors under 75 years is the best predictor of severe or moderate disability at three months (Taub et al, 1994).…”
Section: Incontinencementioning
confidence: 99%
See 1 more Smart Citation
“…Incontinence is a stiong predictor of poor recovery (Gross, 1998;Taub et al, 1994). For example, the presence of incontinence in first-time stroke survivors under 75 years is the best predictor of severe or moderate disability at three months (Taub et al, 1994).…”
Section: Incontinencementioning
confidence: 99%
“…Continence status has also been found to influence the place of discharge (Patel et al, 2001;Taub et al, 1994) although Gross (2000) did not find a significant relationship between continence status at discharge and discharge destination. Incontinence has been found to contribute to self-reported depression (Brittain, 1998) and dramatically increase the relative risk of death (Nakayama et al, 1997;Anderson et al, 1994).…”
Section: Incontinencementioning
confidence: 99%
“…21 For the majority of patients who did not lose consciousness, the study shows significant differences in death and dependency unexplained by case mix in these 12 centers, and the size of the difference is unlikely to be explained by chance, bias, and confounding, as previously explained. This is a real effect, but perhaps we have not controlled for all possible confounding variables.…”
Section: Comparisons Between Centersmentioning
confidence: 52%
“…The level of detail decided on was a balance between those factors known to predict outcome 21 and the feasibility of data collection in 12 centers across Europe in a routine manner. Davenport et al 22 discuss the confounding influence that variations in case mix exert on clinical outcome.…”
Section: Data Collection and Case MIXmentioning
confidence: 99%
“…Despite some methodological weaknesses, the analysis of 78 prospective studies showed a tendency to predict functional independence and improve day-to-day activities after stroke (Kwakkel, et al, 1996;Wade & Hawer, 1987;Taub, et al, 1994;Motto, et al, 1999;Thommessen, et al, 1999;Wyller, et al, 1997;Sveen, et al, 1996). An important factor is the ability to perform everyday activities immediately after the stroke reported by the Barthel index during the first 2 weeks.…”
mentioning
confidence: 99%